Comparison on Microstructure and Properties of Stainless Steel Layer Formed by Extreme High-Speed and Conventional Laser Melting Deposition - Shen, Bowen; Du, Borui; Wang, Miaohui; Xiao, Ning; Xu, Yifei; Hao, Sheng (Frontiers in Materials, 2019)
A new technology named extreme high-speed laser melting deposition is presented in this paper. The deposition speed of this technology is as high as 30m/min, which can promote the deposition efficiency from 0.09m2/h to 0.54m2/h. In addition, surface of EHLMD layer is smoother which can save part of the machining process after deposition and promotes the production efficiency by 6 times. AISI 431 martensitic stainless steel layers were fabricated on 27SiMn substrate by conventional laser melting deposition and extreme high speed laser melting deposition. The macroscopic morphology, microstructure, microhardness and electrochemical corrosion resistance of the two kinds of layers were characterized. The results show that the microstructures of two kinds of layers comprise of martensite dendrite, retained austenite and continuous inter-dendritic eutectic phases. Although results of the XRD test indicate that there are more retained austenite in the EHLMD layer, the microhardnesses of the two kinds of layers are basically the same, in the range of 600HV to 720HV. Corrosion resistance of the EHLMD layer is better than that of the LMD layer because of the higher Cr content and more uniform alloying elements distribution. Therefore, EHLMD can be considered as an effective alternative to electroplating and applied for production and repair of shaft parts in the manufacturing field.